New species and new records of Uropodina from Virginia, USA (Acari: Mesostigmata) - Kontschán, Jenő (Zootaxa, 2017)
Jedediella hoffmani sp. nov. and Trachytes virginiana sp. nov. are described on the basis of specimens from Virginia USA. This paper also presents the first published records of Trachytes balazyi Wiśniewski & Hirschmann, 1994, Discourella gaitlinburgiana Wiśniewski & Hirschmann, 1994 and Discourella modestasimilis Hiramatsu & Hirschmann 1979 from Virginia, and the first record of Discourella modestasimilis from USA.